Preparation of electroless nickel deposition on electrolytic manganese dioxide - Suhaila Mohd. Sanip; Madzlan Aziz; Jamil Yusof; Raizul Azita Abd. Rashid; Regional Conference on Solid State Science and Technology (20th : 2003 : Lumut, Perak) (Skudai : Universiti Teknologi Malaysia, 2003)
42